Intentions to Participate in Adolescent Training Programs : Evidence from Uganda - Bandiera, Oriana; Burgess, Robin; Goldstein, Markus; Gulesci, Selim; Rasul, Imran; Sulaiman, Munshi (2012)
Almost one-third of the population in developing countries is under age 15. Hence improving the effectiveness of policy interventions that target adolescents might be especially important. We analyze the intention to participate in training programs of adolescent girls in Uganda, a country with perhaps the most skewed age distribution anywhere in the world. The training program we focus on is BRAC's Adolescent Development Program, which emphasizes the provision of life skills, entrepreneurship training, and microfinance. We find that girls who are more likely to benefit from the program are more likely to intend to participate. The program attracts girls who are likely to place a high value on financial independence: single mothers and girls who are alienated from their families. The program attracts girls who are more likely to benefit from training: girls who believe they could be successful entrepreneurs but currently lack the quantitative skills to do so. Reassuringly, girls who are in school full-time are less likely to intend to participate. We also find that the program attracts girls from poorer villages but we find no evidence that poorer girls within each village are more likely to want to participate. Finally, girls from villages who have previously been exposed to NGO projects are less likely to intend to participate.